Formulating Black Womanhood: A Study on Beyoncé’s Hip-Hop Song Lyrics in Beyoncé Platinum Edition Album - Ika Ayu Larasati (Rubikon : Journal of Transnational American Studies, 2016)
This article aims at understanding the Black womanhood concept through Hip-Hop song lyrics, since song lyrics are not only a part of art but also a media to express people’s feelings, education, therapy and entertainment. This article also helps the readers to understand that sexuality portrayed in Hip-Hop song lyrics stands for something and has a function because music is related to the social background, message, function, and effect generated from the artwork.The qualitative method and interdisciplinary approach are used in conducting this article, which involves the literature, history, culture, sociology, and to enhance the understanding of multi-ethnic America, especially about Black womanhood. The article starts with introduction, a discussion about African American culture in general. To produce an up to date writing, the article choses the recent popular singer, Beyonce. In finding Black womanhood concepts in Beyonce’s lyrics. One thing that also needs to be highlighted is Black women’s sexuality.The findings are about Black womanhood from Beyonce’s standpoint, such as the Black woman’s self-definition, the sisterhood, the relationship between mother and daughter, and the relationship with Black men. In addition, since it highlights the Black woman’s sexuality in Hip-Hop that is based on Beyonce’s songs, it indicates that recently Black women began to realize that they have power over their own body.Keywords: Black womanhood, sexuality, Hip-Hop music, Lyrics